Valley coherent exciton-polaritons in a monolayer semiconductor. Issue 1 (December 2018) - Dufferwiel, S.; Lyons, T.; Solnyshkov, D.; Trichet, A.; Catanzaro, A.; Withers, F.; Malpuech, G.; Smith, J.; Novoselov, K.; Skolnick, M.; Krizhanovskii, D.; Tartakovskii, A.
Abstract Two-dimensional transition metal dichalcogenides (TMDs) provide a unique possibility to generate and read-out excitonic valley coherence using linearly polarized light, opening the way to valley information transfer between distant systems. However, these excitons have short lifetimes (ps) and efficiently lose their valley coherence via the electron-hole exchange interaction. Here, we show that control of these processes can be gained by embedding a monolayer of WSe2 in an optical microcavity, forming part-light-part-matter exciton-polaritons. We demonstrate optical initialization of valley coherent polariton populations, exhibiting luminescence with a linear polarization degree up to 3 times higher than displayed by bare excitons. We utilize an external magnetic field alongside selective exciton-cavity-mode detuning to control the polariton valley pseudospin vector rotation, which reaches 45° atB = 8 T. This work provides unique insight into the decoherence mechanisms in TMDs and demonstrates the potential for engineering the valley pseudospin dynamics in monolayer semiconductors embedded in photonic structures. The short exciton life time in atomically thin transition metal dichalcogenides poses limitations to efficient control of the valley pseudospin and coherence. Here, the authors manipulate the exciton coherence in a WSe2 monolayer embedded in an optical microcavity in the strong light-matter coupling regime.